2019
DOI: 10.1111/obr.12963
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome‐immune‐metabolic axis in the epidemic of childhood obesity: Evidence and opportunities

Abstract: Obesity epidemic responsible for increase in diabetes, heart diseases, infections and cancer shows no signs of abating. Obesity in children is also on rise, indicating the urgent need of strategies for prevention and intervention that must begin in early life.While originally posited that obesity results from the simple concept of consuming more calories, or genetics, emerging research suggests that the bacteria living in our gut (gut microbiome) and its interactions with immune cells and metabolic organs incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 84 publications
(92 reference statements)
0
28
0
Order By: Relevance
“…The main factors contributing to the growth of the adipose cells have been found to be strictly connected and involved in the so-called “microbiome-immune-metabolic axis”, a series of connections between the gut microbiome, the immune system and metabolic organs as adipose tissue [ 20 ].…”
Section: Pregnancy and Bat In Newborns: The Role Of Fetal Programmingmentioning
confidence: 99%
See 1 more Smart Citation
“…The main factors contributing to the growth of the adipose cells have been found to be strictly connected and involved in the so-called “microbiome-immune-metabolic axis”, a series of connections between the gut microbiome, the immune system and metabolic organs as adipose tissue [ 20 ].…”
Section: Pregnancy and Bat In Newborns: The Role Of Fetal Programmingmentioning
confidence: 99%
“…One of the most studied contributors in fetal adiposity development is the maternal gestational weight gain. Excessive gestational weight gain, in early and mid-pregnancy, has been associated with high birth weight and lower leptin levels in offspring, factors known to increase the risk of overweight later in life [ 20 , 21 , 22 ].…”
Section: Pregnancy and Bat In Newborns: The Role Of Fetal Programmingmentioning
confidence: 99%
“…Regarding antibiotic use, a recent meta-analysis found a small association between antibiotic use during infancy and risk of children becoming overweight or obese (based on weight indices) at older age (OR = 1.05; 95% CI 1.00, 1.11), as previous studies have presented controversial results [ 74 ]. Despite these findings, mechanistic studies using germ-free animal models have confirmed the causal role of gut microbiome in the obesity pathogenesis and the associations between Lachnospiraceae family and adiposity development [ 76 , 77 , 78 , 79 ]. Please see Kincaid et al for a comprehensive review of the literature discussing the most recent animal and human evidence on the interactions between gut microbiome, early life exposures, and obesity onset [ 78 ].…”
Section: Adipose Tissue Developmentmentioning
confidence: 99%
“…Despite these findings, mechanistic studies using germ-free animal models have confirmed the causal role of gut microbiome in the obesity pathogenesis and the associations between Lachnospiraceae family and adiposity development [ 76 , 77 , 78 , 79 ]. Please see Kincaid et al for a comprehensive review of the literature discussing the most recent animal and human evidence on the interactions between gut microbiome, early life exposures, and obesity onset [ 78 ].…”
Section: Adipose Tissue Developmentmentioning
confidence: 99%
“…Several studies have reported that the microbial community extensively impacts host health by influencing intestinal epithelial cell proliferation, local and systemic immunity, and metabolism. Intestinal dysbacteriosis is associated with obesity, inflammatory bowel disease (IBD), nonalcoholic fatty liver disease, and metabolic syndrome [ 1 4 ]. Diet, environment, and host genetics influence the composition of the gut microbiota, and contribute to the high compositional diversity between individuals, which are comparable to unique fingerprints [ 5 8 ].…”
Section: Introductionmentioning
confidence: 99%